Sleep Promotion Program for Improving Sleep Behaviors in Adolescents: A Randomized Controlled Pilot Study - Bindu John; Sumanth Shetty Bellipady; Shrinivasa Undaru Bhat (Scientifica)
Aims. The purpose of this pilot trial was to determine the efficacy of sleep promotion program to adapt it for the use of adolescents studying in various schools of Mangalore, India, and evaluate the feasibility issues before conducting a randomized controlled trial in a larger sample of adolescents. Methods. A randomized controlled trial design with stratified random sampling method was used. Fifty-eight adolescents were selected (mean age: 14.02 ± 2.15 years; intervention group, n=34; control group, n=24). Self-report questionnaires, including sociodemographic questionnaire with some additional questions on sleep and activities, Sleep Hygiene Index, Pittsburgh Sleep Quality Index, The Cleveland Adolescent Sleepiness Questionnaire, and PedsQL™ Present Functioning Visual Analogue Scale, were used. Results. Insufficient weekday-weekend sleep duration with increasing age of adolescents was observed. The program revealed a significant effect in the experimental group over the control group in overall sleep quality, sleep onset latency, sleep duration, daytime sleepiness, and emotional and overall distress. No significant effect was observed in sleep hygiene and other sleep parameters. All target variables showed significant correlations with each other. Conclusion. The intervention holds a promise for improving the sleep behaviors in healthy adolescents. However, the effect of the sleep promotion program treatment has yet to be proven through a future research. This trial is registered with ISRCTN13083118.